1996
DOI: 10.3758/bf03200877
|View full text |Cite
|
Sign up to set email alerts
|

Attentional focusing with quantifiers in production and comprehension

Abstract: There is a very large number of quantifiers in English, so many that it seems impossible that the only information that they convey is about amounts. Building on the earlier work of Moxey and Sanford (1987),we report three experiments showing that positive and negative quantifiers focus on different subsets of the logical possibilities that quantifiers allow semantically. Experiments 1and 2 feature a continuation task with quantifiers that span a full range of denotations (from near ()OJ6 to near 100%) and sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
59
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(69 citation statements)
references
References 12 publications
(14 reference statements)
10
59
0
Order By: Relevance
“…Striking confirmation of this line of argument is provided by a more recent study contrasting not quite N% with nearly N% where N ranged from 10 to 90 (Sanford, Moxey & Patterson 1996). (This study will be more fu lly discussed in section 4).…”
Section: Critique Of the Generic Accountsupporting
confidence: 58%
See 1 more Smart Citation
“…Striking confirmation of this line of argument is provided by a more recent study contrasting not quite N% with nearly N% where N ranged from 10 to 90 (Sanford, Moxey & Patterson 1996). (This study will be more fu lly discussed in section 4).…”
Section: Critique Of the Generic Accountsupporting
confidence: 58%
“…would also apply to expressions of the form not quite all, not quite N% which are shown by (Sanford, Moxey and Patterson 1996) to produce compset continuations, in contrast to nearly N% which is virtually indistinguishable from not quite N% as far as truth-conditions are concerned.…”
Section: Alternative Readingsmentioning
confidence: 99%
“…For example, a proposition can convey information about a group of individuals, but differing quantifiers can direct the readers' attention to the good or the bad aspects, as in Few of the patients were critically ill (which is good), or A few of the patients were critically ill (which is bad). Different patterns of pronominal reference have been revealed for positive and negative quantifiers in continuation tasks (e.g., Moxey & Sanford, 1987;1993a;Sanford, Moxey & Paterson, 1996). Following a negative quantifier, continuations typically refer to the Complement Set (i.e.…”
Section: Few)mentioning
confidence: 99%
“…However, negative quantifiers alone license negative polarity items such as anymore. Moxey and Sanford (1987) and Sanford, Moxey, and Paterson (1996) showed that positive and negative quantifiers differ in their focus properties, as illustrated in (2)-(3). Whereas the positive quantifiers in (2) focus attention on the fans that went to the game, the negative quantifiers in (3) focus attention on the fans that did not go to the game, as the continuations make clear.…”
mentioning
confidence: 99%
“…Importantly, the set that is in focus does not depend on the amount denoted by the quantifier. Sanford et al (1996) had participants indicate the proportions they thought quantifiers denoted in 30 different contexts, and found that few (negative) and a few (positive) denoted about 14%, while not quite all (negative) and nearly all (positive) both denoted 95%. But in attribution studies all quantifiers denoting small amounts (hardly anyone, few, not.…”
mentioning
confidence: 99%